Girl, woman, other - Evaristo, Bernardine, 1959- (London, United Kingdom : Penguin Books, 2020)
"Girl, Woman, Other is a celebration of the diversity of Black British experience. Moving, hopeful, and inventive, this extraordinary novel is a vivid portrait of the state of contemporary Britain and the legacy of Britain's colonial history in Africa and the Caribbean. The twelve central characters of this multi-voiced novel lead vastly different lives: Amma is a newly acclaimed playwright whose work often explores her black lesbian identity; her old friend Shirley is a teacher, jaded after decades of work in London's funding-deprived schools; Carole, one of Shirley's former students, works hard to earn a degree from Oxford and becomes an investment banker; Carole's mother Bummi works as a cleaner and worries about her daughter's lack of rootedness despite her obvious achievements. From a nonbinary social media influencer to a 93-year-old woman living on a farm in Northern England, these unforgettable characters also intersect in shared aspects of their identities, from age to race to sexuality to class. Sparklingly witty and filled with emotion, centering voices we often see othered, and written in an innovative and fast-moving form that borrows from poetry, Girl, Woman, Other is a polyphonic and richly textured social novel that reminds us of everything that connects us to our neighbors, even in times when we are encouraged to be split apart"--
AAL
Winner of the Man Booker Prize for Fiction, 2019.
Keywords: African American women -- Fiction; Women, Black -- Great Britain -- Fiction; English fiction; Great Britain -- Social life and customs -- Fiction